Reporting Antarctica: how the news media frames Antarctic science in a changing climate - Hunt, L (Scientific Committee on Antarctic Research (SCAR), 2020)
For the majority, Antarctica is a mysterious frozen continent: a place of science and internationalcollaboration; and a symbol of fears about global warming. But from where do these ideas generate andwho decides the terms of reference for the publics understanding of Antarctic science? The role of newsmedia has been largely overlooked in scholarship, which seeks to understand public engagement with, andunderstanding of, the Antarctic region. This is a significant gap in research, given that the news media is thepublics main source of information about science. As images of calving icebergs and collapsing ice shelvesbecome more commonplace on news feeds, news medias role in framing key issues such as climate changedeserves exploration. Using the Australian news media as a case study, data collected from Australianonline news media outlets over a recent 12-month period will be analysed to identify prominent frames andvoices in news discourse related to Antarctic science. The data will be considered in light of existingscholarship which examines the role of journalists as gatekeepers of science stories and the politicisation ofscience. This presentation argues that exploring journalistic representations of Antarctica science has thepotential to challenge assumptions about the role of news media and scientists in communicating issuessuch as climate change.